Jogos didáticos no ensino de química como mediadores na mobilização da atenção de alunos com diagnósticos de TDAH no ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The purpose of this essay is to investigate the use of Didactic Games on Chemistry Classes, mobilizing voluntarily the attention of students diagnosed with ADHD of the Center for Comprehensive Education John XXIII High School in Ceres Go. The current research makes a critical reflection about the diagnosis of ADHD as being from a genetic origin and capable of causing symptoms like inattention, hyperactivity and impulsivity. Many experts had noted in this diagnosis a medicalization process for school failure.Vygotsky´s historical-cultural theory shows that attention and learning problems occur as a result of social, political and educational problems. The theory has as specific targets identify the conceptions of the teachers of Natural Sciences and Mathematics on the diagnosis of ADHD, as well as to verify with the students diagnosed with ADHD their understanding about the teaching and learning of Natural Sciences and Mathematics. It also proposes a didactic game on Chemistry teaching to get students attention to scientific knowledge. Thenceforth, it was possible to verify the voluntary mobilization of student‟s attention on didactic game. The game on Chemistry teaching is a mediating possibility for voluntary attention mobilization that has not been developed yet. The ludic can develop in the students diagnoses with ADHD and also in the other students the scientific knowledge in a pleasant, interactive and cultural way in the process of teaching and learning. The research sample consists of full time teachers and students of the Center of Education in Ceres, Goiás, though a semistructured interview. The objectives of the research were achieved through qualitative research methodology. For data analysis it was used the Lawrence Bardin content analysis. Based on data collected, it was possible to see that playful activities, such as the didactic games, could mobilize the attention of all students on the scientific knowledge of teaching and learning. Based on the data collected, it can be seen that playful activities, like didactic game, mobilize the student‟s attention to the teaching and learning of scientific knowledge in a fun and enjoyable way. It favors the intellectual development, the social interaction and language. This research contributed to the reflection of the use of didactic games as a mediator in the mobilization of the attention in students diagnosed with ADHD based on the historical-cultural theory of Vygotsky.
Keywords: Ensino de Ciências - Matemática; Teoria histórico-cultural de Vigotski; TDAH; Ensino de Química - Jogos didáticos; Teaching Science and Mathematics; Historical-cultural theory of Vygotsky; ADHD; Didactic games in teaching Chemistry; CIENCIAS EXATAS E DA TERRA::QUIMICA; EDUCACAO::ENSINO-APRENDIZAGEM